Momento de dipolo magnético de neutrinos - Costa, Barbara Sales (2022)
Neutrino Physics has been going through a real boom since the neutrino oscillations were detected, thus confirming that they are massive particles. This discovery opened up many physics possibilities beyond the Standard Model, among them the Magnetic Dipole Moment (MDM) divergence of Neutrinos. While the original Standard Model had the neutrino MDM as null, more recent models give us a theoretical prediction of an MDM on the order of 10-19µB, but experiments so far give us µν < 10-10µB, which is still 9 orders of magnitude higher than expected, opening the way for new physics to be explored by proposing MDM generating models for neutrinos that align the theoretical prediction with the experimental one. In this way, we started the work by making a historical overview of particle physics, especially about neutrinos, and then making a review about the Electric Dipole Momentum (EDM) and MDM of electrons. We also discuss the MDM of neutrinos in the Standard Model and in the currently best accepted model and soon after we propose a Lagrangian of interaction generating MDM for the neutrinos and from it we calculate the cross section for electron-neutrino scattering and then compare our theory with the experimental data collected by MicroBooNE.